Children in Custody Disputes: Matching Legal Proceedings to Problems: Book Review - Wahyu Ram Laksono (Contemporary Islamic Law and Legal Issue, 2026)
Children in Custody Disputes: Matching Legal Proceedings to Problems by Kaldal, Hellner, & Mattsson (2024) offers a comprehensive and interdisciplinary examination of how legal systems respond to conflicts over child custody, residence, and contact following parental separation. Bringing together scholars from law, social sciences, psychology, and procedural studies, the book addresses the growing recognition that custody disputes are not merely legal disagreements but complex social and emotional conflicts with profound consequences for children’s wellbeing. The volume situates these disputes within contemporary legal frameworks influenced by children’s rights, particularly the principles of the best interests of the child and the child’s right to participation.